Reliability study on the adaptation of Dijkstra’s algorithm for gateway KLIA2 indoor navigation - K. A. F. A. Samah; A. A. Sharip; I. Musirin; N. Sabri; M. H. Salleh (Bulletin of Electrical Engineering and Informatics, 2020)
This paper describes a reliability study on the adaptation of Dijkstra’s algorithm (DA) in the indoor environment for navigation purposes. Gateway KLIA2 located at Sepang, Selangor, Malaysia has been chosen as the area for case study. Gateway KLIA2 is divided into 4 levels but this research focused on Level 2 only that consists of 129 shop lots. A survey conducted towards 68 public respondents before the adaptation and most of them responded that they are not aware of the surrounding of KLIA2 and are facing difficulties in finding the information or location of certain places inside the building. DA was chosen because it helps the users to navigate using the shortest path to destination. It is proven that through the adaptation of DA, we are able to provide the shortest distance for indoor navigation from current location to the destination location. G-INS is reliable based on the functionality and reliability testing conducted towards 15 users with the distance reduction of 47% t-test result of 0.01303 (p less than 0.05), indicates the system is accepted.